A cross sectional study to estimate the prevalence of vitamin B12 deficiency among type 2 diabetes cases on metformin therapy: a one year study - Gundu, Veeranarayana; Chintha, Venkata Subrahmanyam (International Journal of Advances in Medicine, 2021)
Background: Type 2 diabetes mellitus is associated with long term neurological complications. Metformin usage as first line drug for longer duration is associated with Vitamin B12 deficiency. Metformin on longer usage is associated with B12 deficiency in various studies and prevalence is variable. The study aims to estimate the prevalence of Vitamin B12 deficiency and its associated risk factors among T2DM on metformin therapy. Methods: A cross sectional study for one year was conducted at Narayana Medical college a tertiary care hospital. All T2DM cases attending the department and on Metformin usage were enrolled and data of age, sex, duration of T2DM, dosage of Metformin were noted as variables. Levels of Hb1Ac and complete blood picture were noted. Statistical analysis was conducted by Statistical package for social sciences (SPSS) version 21 v and p<0.05 was considered statistically significant. Results: A total of 258 participants were enrolled of which 68 (26.36%) were B12 deficient, 46 cases (17.83%) moderately deficient and 144 (55.81%) were normal. Prevalence of Vitamin B12 in the study was 26.36%. There was a statistically significant association between Vitamin B12 levels and daily dose of metformin usage. (p>0.005) Conclusions: Our study clearly highlighted the association of Vitamin B12 deficiency among T2DM on metformin therapy. Prevalence of Vitamin B12 deficiency among T2DM patients on metformin is quite considerable and cannot be neglected. Physicians prescribing the drug should plan inclusion Vitamin B12 supplementation as regular drug in T2DM cases.